Mechanical properties of tin mine tailing sand for greensand casting mould - Abdullah, Azhar (2012)
Tailing sand is the residue from tin extraction, containing between 94% to 99.5% silica. It is abundant especially in Kinta Valley of state of Perak, Klang Valley of state of Selangor and certain areas in Johor, Negeri Sembilan and Pahang in Peninsular Malaysia. Many abandon tailing sand dump areas are easily to access due to the reason of transportation of tin and at present most of them have been covered by bushes even though there are efforts to convert the land for agriculture, industrial and housing estate. The worst scenario is issue of illegal activities of tailing sand mining including sand stealing. The purpose of this research is to investigate the mechanical properties of tailing sand as aggregate for making greensand casting mould. Five samples from Tronoh and Tanjung Tualang in Perak state; Batang Berjuntai in Selangor; Jemaluang in Johor and Gambang in Pahang were gathered. The experiments for this investigation are strictly obeying the American Foundrymen Society (AFS) standard of procedures. The investigation involved the process of; identifying locations for sampling of tailing sand with high content of silica in Peninsular Malaysia, conducting the mechanical sieve grading to identify the size spread, plotting the grain size distribution and calculating the average grain size. Further on with classifying the grain shape, the clay grade, the effects of controlled additions of clay (bentonite) and water and determining the working range on the mechanical moulding properties of tailing sand. The investigation involved comparing the mechanical properties of the tailing sand to mould sand taken from RCS Manufacturing Sdn. Bhd., the company supplying mould sand to the Proton Casting Plant, manufacturer of engine components in Malaysia and the requirement for foundry sand applications listed by Foseco Ferrous Foundryman‟s Handbook (Foseco). The size spread, grain size distribution, average grain size and grain shape of tailing sand matched the Foseco requirement and RCS, which are well sorted and uniform, within the required size (217 to 281 μm) and has sub angular with compound sphericity shape. Test on the clay grade showed that clay grade is between 0.47% -2.07%, which resembles the true clay value in the sand. Cylindrical test piece specimens dimensioning of Ø50 mm×50 mm in height from various sand–clay-water ratios, were produced by applying three ramming blows of 6.666 kg each using Ridsdale-Dietert metric standard rammer. The specimens were tested for green compression strength using Ridsdale-Dietert universal sand strength machine and permeability number with Ridsdale-Dietert permeability meter. Before the tests were conducted, the moisture content was measured using AND MX50 moisture analyser. The working range for samples with 2.9% by weight (wt) of water addition were at allowable clay content ranged from 2.5-5.0wt% where green compression strength ranged from 25 kN/m2 to 43 kN/m2 and permeability number from 63 to 225. The samples with 4.8wt% of water addition have the working range at the allowable clay content ranged from 4.0-6.5wt% where the green compression strength ranged from 35 kN/m2 to 52 kN/m2 and permeability number from 76 to 252. The working range for samples bonded with 3.8wt% of clay were at allowable moisture content ranged from 3.0-4.0wt% where the green compression strength ranged from 20 kN/m2 to 48 kN/m2 and permeability number from 90 to 255. If bonded with 7.4wt% clay, the allowable moisture content ranged from 3.5-6wt% where the green compression strength ranged from 33 kN/m2 to 70 kN/m2 and permeability number from 70 to 220. Finally, the investigation indicated that tailing sand is suitable as foundry sand for making greensand casting mould where the allowable clay and moisture content of tailing sand samples are within the range in application for making greensand casting mould for ferrous and non-ferrous metal.